Cellulose nanomaterials isolated via enzymatic and mechanical routes for application in hydrogels - Carvalho, Paula Squinca de (Universidade Federal de São Carlos, 2021)
The integrated production of different bioproducts has been considered essential to make biorefineries economically viable. Among the bioproducts, cellulose nanomaterials (CNs) have attracted significant attention due to their attractive properties and wide spectrum of applications. The use of enzymes to isolate cellulose nanomaterials have gained growing interests mainly associated with the milder operational conditions and the selectivity and specificity of these biocatalysts. However, the available commercial enzymatic preparations are not optimized for this purpose yet. Besides, exploiting agro-industrial residues as feedstock to nanomaterials production is another advantageous strategy from environmental and economic point of views. Within this context, cellulose nanomaterials were isolated through enzymatic and mechanical routes for applications in manufacture of hydrogels. Enzymes were produced by Aspergillus niger under solid-state fermentation and applied to obtain the CNs via enzymatic hydrolysis followed by sonication using eucalyptus cellulose pulp as a model feedstock. The condition that resulted in the highest yield of cellulose nanocrystals isolation was determined through central composite rotational design and the nanomaterials presented high crystallinity index and good thermal stability. The ginger residue was used as feedstock to obtain cellulose nanofibrils (CNFs) by mechanical treatment and applied to prepare hydrogels through vacuum-assisted filtration. The hydrogels presented transparency, biocompatibility, tunable liquid absorption, flexibility combined with good mechanical stability in moist conditions, and antimicrobial performance showing to be promising materials for wound dressing applications. In the final part of the thesis, cellulose nanomaterials produced with commercial and non-commercial enzymes were incorporated into gelatin-based hydrogels which were prepared by solvent casting using tannic acid as crosslinker and ginger essential oil to increase the antimicrobial properties. The hydrogels inhibited the growth of Staphylococcus aureus and Escherichia coli and the cellulose nanomaterials obtained with non-commercial enzymes better contributed to their structural integrity. These results provided a proof of concept that cellulose nanomaterials can be efficiently obtained using non-commercial enzymes and applied in hydrogel manufacture. Meanwhile, for an already established route, hydrogels totally based on nanofibrils extracted from ginger showed important properties to be used as wound dressing.
Nanomateriais celulósicos isolados via rotas enzimática e mecânica para aplicação em hidrogéis
Keywords: Desenvolvimento sustentável; Hidrólise enzimática; Enzimas não comerciais; Gengibre; Hidrogéis; Sustainable development; Enzymatic hydrolysis; Non-commercial enzymes; Ginger; Hydrogels; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA